Patient-held health IT adoption across the primary-secondary care interface: a Normalisation Process Theory perspective. Issue 1 (2nd January 2022) - McCarthy, Stephen; Fitzgerald, Ciara; Sahm, Laura; Bradley, Colin; Walsh, Elaine K
ABSTRACT: Patient-held Health Information Technologies (HIT) can reduce medical error by improving communication between patients and the healthcare team. Despite the proposed benefits, the roll-out of patient-held HIT solutions remains nascent, leaving considerable gaps in our understanding of the adoption challenges inherent. This paper adopts Normalisation Process Theory to study the factors which support or impede the adoption and "normalisation" of patient-held HIT, particularly across the primary-secondary care interface. The authors conducted an in-depth case study of HIT adoption across four GP practices, and the wards of a 350 bed hospital. 35 semi-structured interviews were completed. Findings point towards both user-specific and network-specific factors as significant challenges to normalisation across primary-secondary care. This includes factors related to interactional workability, skill set workability, relational integration, and contextual integration. We also discuss challenges specific to patient-held HIT adoption e.g., understanding the patient/clinician experience, supporting informal clinician networks, and spanning across IT boundaries.